Physicochemical Properties and Nutritional Composition of Chicken Patties with Grey Oyster Mushroom Stems - Sayeed Ibrahim, H. S.; Huda-Faujan, N. (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (50-57)